Comparison of Liquefaction-Induced Damage Observed During the 2011 Christchurch (New Zealand) and 1990 Luzon (Philippines) Earthquake - Orense, Rolando P. (Philippine Engineering Journal; Vol 32 No 1 (2011), 2021)
Soil liquefaction and associated ground deformations caused extensive damage to residential buildings and lifelines facilities in many areas in Christchurch City(New Zealand) during the 2010 and 2011 Canterbury Earthquakes. Twenty years earlier, the 1990 Luzon (Philippines) earthquake also caused widespread in Dagupan City due to liquefaction. This paper compares the liquefaction-induced damage observed in both earthquakes, with emphasis on the characteristics of the sites affected by liquefaction, the extent of ground deformations observed and the influence of liquefaction-induced settlement and lateral spreading on the build environment. Moreover, cases of successive re-liquefaction observed in soul deposits in Christchurch over a span of nine months are discussed.